2014
DOI: 10.1111/jgh.12712
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of hepatitis B vaccine in patients with inflammatory bowel disease and the benefits of revaccination

Abstract: One hundred seventy-two patients were included and received the first HBV vaccine schedule. Eighty-seven developed anti-HBs ≥ 10 mIU/mL (50.6%; 95% confidence interval [CI]: 42.9-58.3). From the non-responders, 53 were revaccinated and 28 showed an adequate serological response (52.8%; 95% CI: 38.6-66.7). Age older than 55 years (OR: 3.6; 95% CI: 1.3-10.2) and comorbidities (OR: 2.8; 95% CI: 1.1-7.1) were associated with suboptimal response. In the multivariate analysis, only age was a predictor of non-respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 35 publications
(43 reference statements)
2
27
1
1
Order By: Relevance
“…Two diseases do not seem to differ with respect to immune response to HBV vaccine both in our study and other studies. 14 , 19 , 21 IBD disease location had no significant effect on immune response to HBV in our study. There was no relationship between disease location and immune response in CD, but there was a significant difference between CD subtypes.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Two diseases do not seem to differ with respect to immune response to HBV vaccine both in our study and other studies. 14 , 19 , 21 IBD disease location had no significant effect on immune response to HBV in our study. There was no relationship between disease location and immune response in CD, but there was a significant difference between CD subtypes.…”
Section: Discussioncontrasting
confidence: 56%
“…Immune response rates obtained with HBV vaccination in IBD are known to be lower compared with healthy populations, but different results were reported from a few studies on this subject (Altunöz 76%, Gisbert 41%, and Cossio-Gil 50%). 14 , 18 , 19 These different results may be explained by the different characteristics of the patient groups across studies with regards to factors that are influential on immune response including immunosuppressive therapy (IST) and disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…This deserves further studies because such individuals are children or younger adults. Several earlier studies have already demonstrated that individuals with anti-HBs seronegativity would be at increased risks of contracting HBV infections even at 20 years of the vaccination (3334). This is noteworthy in HBV-endemic areas, including Korea, which has also been supported by several published studies.…”
Section: Discussionmentioning
confidence: 99%
“…The indicated vaccinations in older IBD patients include the annual influenza flu vaccine, the pneumococcal vaccine administered at the age of 65, and the zoster vaccine after age 60. Importantly, vaccination is more likely to be associated with a suboptimal response in the elderly, especially in the setting of immune suppression [84][85][86].…”
Section: Vaccinationsmentioning
confidence: 98%